2021
DOI: 10.20873/jbb.uft.cemaf.v9n2.maldonaro
|View full text |Cite
|
Sign up to set email alerts
|

Application of tamarind pulp for wine production

Abstract: Tamarind (Tamarindus indica L.) is a nutrient-rich fruit that has an acid and exotic flavor. It is widely consumed in natura at tropical countries such as India and Brazil. The aim of this study was to evaluate the application of tamarind as a substrate for the production of tamarind wine. The pulp from ripe fruits was used to produce wine in three different proceedings: (1) whole pulp, (2) pulp without insoluble solids and (3) pulp without insoluble solids and pH adjusted to 4.5. In all cases, the fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, the prevalence of allergy to cows' milk proteins, lactose, and gluten intolerance, as well as the popular trends towards vegan and vegetarian diets, have promoted an accelerated development of A-FB, LA-FB, and NA-FB with non-traditional ingredients as an alternative to satisfy the mentioned needs. Hence, scientific interest in the design of fermented beverages with non-conventional ingredients and health-related properties and the selection of optimal processing conditions has increased during the last decade [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Fermented Beverages Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the prevalence of allergy to cows' milk proteins, lactose, and gluten intolerance, as well as the popular trends towards vegan and vegetarian diets, have promoted an accelerated development of A-FB, LA-FB, and NA-FB with non-traditional ingredients as an alternative to satisfy the mentioned needs. Hence, scientific interest in the design of fermented beverages with non-conventional ingredients and health-related properties and the selection of optimal processing conditions has increased during the last decade [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Fermented Beverages Developmentmentioning
confidence: 99%
“…Recently, Maldonado et al [20] used tamarind (Tamarindus indica L.) as a substrate for tamarind wine production, using S. cerevisiae for fermentation. These authors indicated that tamarind is a potential alternative for wine production, improving the utilization of this fruit.…”
Section: Fermented Beverages Developmentmentioning
confidence: 99%